2016
DOI: 10.1371/journal.pone.0157349
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation of Limb Proprioceptive Afferents Decreases Apnea of Prematurity and Accompanying Intermittent Hypoxia and Bradycardia

Abstract: BackgroundApnea of Prematurity (AOP) is common, affecting the majority of infants born at <34 weeks gestational age. Apnea and periodic breathing are accompanied by intermittent hypoxia (IH). Animal and human studies demonstrate that IH exposure contributes to multiple pathologies, including retinopathy of prematurity (ROP), injury to sympathetic ganglia regulating cardiovascular action, impaired pancreatic islet cell and bone development, cerebellar injury, and neurodevelopmental disabilities. Current standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 80 publications
(75 reference statements)
0
35
0
Order By: Relevance
“…The mean/median GA varied between studies from 28 to 32.1 weeks. Three studies reported the GA at the start of the study, ranging from 32 to 35 weeks ( 14 , 25 , 26 ) and five studies reported the (mean/median) age when the study started, ranging from 4.3 to 35 days after birth ( 27 – 31 ). The mean/median birth weight also differed between studies from 1,080 to 1,760 g. Three studies reported a mean weight of 1,264–2,013 g at the start of the study ( 14 , 26 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean/median GA varied between studies from 28 to 32.1 weeks. Three studies reported the GA at the start of the study, ranging from 32 to 35 weeks ( 14 , 25 , 26 ) and five studies reported the (mean/median) age when the study started, ranging from 4.3 to 35 days after birth ( 27 – 31 ). The mean/median birth weight also differed between studies from 1,080 to 1,760 g. Three studies reported a mean weight of 1,264–2,013 g at the start of the study ( 14 , 26 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean/median birth weight also differed between studies from 1,080 to 1,760 g. Three studies reported a mean weight of 1,264–2,013 g at the start of the study ( 14 , 26 , 29 ). In a number of studies (some of) the infants were supported by means of: administered caffeine ( 14 , 25 , 26 ), theophylline ( 28 , 30 , 32 , 33 ) or antibiotics ( 29 ), supplemental oxygen ( 14 , 25 , 26 ), and continuous positive airway pressure or assisted ventilation ( 27 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…43,44 • Several other nonpharmacological approaches have been tested, albeit with mixed results. These include physical stimulation, 45,46 olfactory stimulation, 47 and sound stimulation using maternal sounds. 48 Other interventions such as increased low dose inspired CO 2 49 and red blood cell transfusions 50,51 have been suggested for AOP, though current evidence does not support their routine use.…”
Section: Treatment Of Apnea Of Prematuritymentioning
confidence: 99%